Expression of PD-L1 in primary breast carcinoma and lymph node metastases - Alice M. Alves; Joana Paredes; Fernando Schmitt (BMC, 2019)
Abstract Background Programmed cell death ligand 1 (PD-L1) is a predictive biomarker of the response of immunotherapy in some types of cancer. In the last years it was described its expression in breast cancer, namely in triple-negative breast cancer (TNBC) cases. In order to better understand the prognostic value of PD-L1 in breast cancer, this study analysed its expression in a series of primary tumours and respective nodal metastases. Methods PD-L1 expression was evaluated by immunohistochemistry in a series of 52 breast cancer cases and paired lymph node metastasis and correlate with the clinicopathological features of the primary tumour. The TNBC cases were re-classified using morphological and immunohistochemistry surrogate markers and the expression of PD-L1 was correlate with the different subtypes. Results It was observed that the majority of the cases with PDL-1 positive in the nodal metastasis did not express PD-L1 in the primary tumour (90.0%, 10 out of 11 cases). In addition, from the cases with a negative PD-L1 expression in the primary tumour, 23.8% expressed PD-L1 in the metastasis (10 out of 42 cases).No relationship was found between the PD-L1 expression in nodal metastasis and the clinicopathological features of the primary tumour. Finally, basal-like immunosuppressed (BLIS) TN tumours seem to be less prone to express PD-L1. Conclusion Although without statistical significance, there is a gain in terms of the PD-L1 expression in the nodal metastasis when compared to the primary tumour. This may have therapeutic implications on immunotherapy that blocks the PD-1/PD-L1 pathway.